2016
DOI: 10.1136/archdischild-2016-311135
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the introduction of rotavirus vaccination on paediatric hospital admissions, Lothian, Scotland: a retrospective observational study

Abstract: These results provide encouraging initial evidence of the public health benefit, including to the unimmunised population, of the RV vaccination programme in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…It is likely that using these codes will miss a proportion of rotavirus cases as they are likely to be coded under general acute gastroenteritis codes. 15 Our finding of a 40% reduction in hospital admissions is in line with a the 44% reduction found in a study of five local authority areas in Merseyside, England over the period 2013-2016 (consisting of five hospitals with emergency and secondary care facilities and a paediatric hospital). 16 We found that the impact of the vaccine in primary care was lower than that predicted by Jit et al (2007), with a substantial proportion of overall reduction in healthcare cost due to a decrease in GP consultations.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It is likely that using these codes will miss a proportion of rotavirus cases as they are likely to be coded under general acute gastroenteritis codes. 15 Our finding of a 40% reduction in hospital admissions is in line with a the 44% reduction found in a study of five local authority areas in Merseyside, England over the period 2013-2016 (consisting of five hospitals with emergency and secondary care facilities and a paediatric hospital). 16 We found that the impact of the vaccine in primary care was lower than that predicted by Jit et al (2007), with a substantial proportion of overall reduction in healthcare cost due to a decrease in GP consultations.…”
Section: Discussionsupporting
confidence: 88%
“…12,13 Prior to the introduction of the rotavirus vaccination programme, the Scottish Government predicted that such a programme could reduce the number of rotavirus-related hospital stays by approximately 70%. 14 Forrest et al (2017) found a reduction of 85% and 91% in rotavirus related admissions and bed-days, respectively, in a paediatric hospital setting in Lothian, Scotland. 15 This study used a highly specific definition of rotavirus-based admissions based on positive laboratory reports so is comparable with the 73% reduction suggested by our study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This can lead to potential diagnostic delays and confusion in clinical practice (Forrest et al, 2017), while misclassification of cases risks underestimating effectiveness of vaccine programs (Tate et al, 2013). Additional complexity is provided when PCR detects wild-type rotavirus in asymptomatic children (Amar et al, 2007) and for up to 8-weeks after recovering from gastroenteritis (Richardson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study involved only infants receiving RotaTeq, which does not replicate as well in the gastrointestinal tract as Rotarix, the widely used single, live-attenuated, humanderived G1P[8] strain (Anderson, 2008). The limited data available however, suggest that Rotarix is shed in higher quantities and potentially for longer periods than RotaTeq (Hsieh et al, 2014;Forrest et al, 2017;Anderson, 2008). Hsieh and the colleague found that the mean Rotarix vaccine virus shedding load in vaccine recipients was 1.7x10 9 genome copy number/g stool, and which was 100 fold-higher than RotaTeq vaccine viruses in RotaTeq vaccine recipients.…”
Section: Discussionmentioning
confidence: 99%